Triangular Causality and Controlling Parallel Exchange Market - Bidabad, Bijan (Australian Finance & Banking Review, 2019)
In this paper, the triangular relationship of money, price, and foreign exchange in a causality context are studied. It is concluded that regulating the exchange rate by volume of liquidity in a period of less than a year is not possible, but in annual and biannual analyses we can regulate the exchange rate through controlling the liquidity. In other words, in the long run, the exchange rate is affected by liquidity and price level, but in the short run, the price level has only temporary effects on the exchange rate. The results of the study show that: liquidity affects the exchange rate in the long run; price affects the liquidity in the long run; in the long run, liquidity and exchange rate affect prices. Our results show that injection of foreign exchange into the parallel exchange market with different lags has little effects with different directions on the exchange rate. The same result is true for the relationship between liquidity and dollar rate. In other words, in spite of the long run relationship between exchange rate and liquidity, we cannot justify this relationship in the short run. The same is true with the balance of payments position and exchange rate in the short run.By simulating the relationship between injecting (selling) foreign exchange in the parallel exchange market, liquidity and the cumulative balance of payments all with exchange rate, we can conclude that in the short run, regulating exchange rate by instruments such as selling exchange in the parallel market or controlling the liquidity is not possible, but in the long run, conducting foreign exchange sale policy and controlling the liquidity and the balance of payments position can control the exchange market.